INSTYTUCJA PRZEDSTAWIENIA ZARZUTÓW I JEJ KONSEKWENCJE PROCESOWE - Kaczorkiewicz, Dorota; Tarnowska, Danuta (Wydział Prawa i Administracji UAM, 2011)
Publikacja przedstawia historię kształtowania się w polskim ustawodawstwie instytucji przedstawienia zarzutów, która pojawiła się w polskiej procedurze karnej w 1950 r., a także jej obecny kształt i znaczenie w postępowaniu przygotowawczym. Wskazano także konsekwencje, jakie wywołuje w postępowaniu karnym przedstawienie osobie zarzutów, jak również omówiono te instytucje procesowe, które są z nim związane zarówno w sferze realizacji praw oskarżonego do obrony oraz działań organów procesowych, jak i innych uczestników postępowania karnego.

*The authors outline the history of the institution of presenting charges under Polish criminal proceedings. The presentation of charges as an institution appeared in Polish proceedings already in the 1950’s and since then the suspects have been informed about their rights. However, the institution itself has undergone a number of subsequent amendments. Currently, presenting charges entails many actions to be taken by the person who conducts preparatory proceedings. These actions require a particular form of investigation. And so, for example, the decision of the presentation of charges must have a written form. What is more, it must be read out to the suspect. Then, the suspect is to be interrogated. The charges are subject to alteration during the preparatory proceedings. After the charges have been presented, the person involved becomes a suspect. The presentation of charges gives rise to many legal effects which are also discussed in the paper.
PRESENTATION OF CHARGES AND ITS CONSEQUENCES IN CRIMINAL PROCEEDINGS
Keywords: Postępowanie przygotowawcze; Preparatory proceedings; Przedstawienie zarzutów; Informing the suspect; Prawa podejrzanego; Rights of suspect